2016
DOI: 10.1016/j.clinthera.2016.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Using Patient-reported Outcomes to Compare Relative Burden of Cancer: EQ-5D and Functional Assessment of Cancer Therapy-General in Eleven Types of Cancer

Abstract: The overall and dimension-specific HRQL burden of advanced cancer depended on the type of cancer. Such results may aid clinicians and patients in better understanding of how cancer site can affect HRQL and functioning in different ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…Asking a patient to provide PROs in terms of symptoms [17] and questionnaires [4] represents a powerful means not only to ascertain the severity of a disease, but also to accomplish a functional assessment on the patient. A functional assessment may have a strong prognostic influence on the disease evolution, in particular for cancer patients, and may be used either to adjust the treatment or to prepare and support a shared decision-making process during the next scheduled visits [18].…”
Section: Requirement Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Asking a patient to provide PROs in terms of symptoms [17] and questionnaires [4] represents a powerful means not only to ascertain the severity of a disease, but also to accomplish a functional assessment on the patient. A functional assessment may have a strong prognostic influence on the disease evolution, in particular for cancer patients, and may be used either to adjust the treatment or to prepare and support a shared decision-making process during the next scheduled visits [18].…”
Section: Requirement Analysismentioning
confidence: 99%
“…Data provided by patients are called Patient-reported outcomes (PROs), and have been proved very useful to assess the patients' conditions, enhance the clinician awareness and improve symptom management. They usually include physical parameters (e.g., pain, weight and blood pressure), psychosocial symptoms (e.g., fatigue, anxiety and depression), functional assessment scores [4,5], or Quality of Life (QoL) scores [6,7]. Customarily, patients simply keep a paper diary in which they annotate on a daily basis the parameters required by the clinicians or the problems that occur.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer, and its surgical, radiotherapy, and chemotherapy treatments, can cause debilitating symptoms and consequent problems with day‐to‐day functioning . Symptoms often arise up to a year after treatment.…”
Section: Introductionmentioning
confidence: 98%
“…8,9 Cancer, and its surgical, radiotherapy, and chemotherapy treatments, can cause debilitating symptoms and consequent problems with day-to-day functioning. 10,11 Symptoms often arise up to a year after treatment. Thus, symptom occurrence and any effects of those symptoms on anxiety or depression will not be captured in research that measures predictors shortly after diagnosis or treatment.…”
mentioning
confidence: 99%
“…Sex differences in QOL for cancer patients have been previously observed and studies frequently adjust for age and sex differences that can impact QOL. [12][13][14] While the current findings need to be validated by other studies of brain metastasis patients, the sex differences found herein as related to pain and discomfort may be cause for increased recognition and, if present, medical treatment in men suffering from these problems during the course of their care for brain metastasis. Lastly, the study suggests that anxiety subscores at baseline are frequently predictive of anxiety subscores at last follow-up.…”
Section: Discussionmentioning
confidence: 54%